PERAN ORANG TUA DALAM MEMBENTUK KARAKTER BERTANGGUNG JAWAB ANAK DI JORONG SIDOMULYO KECAMATAN PULAU PUNJUNG KABUPATEN DHARMASRAYA - Mufliah, Tri Hidayati (Bimbingan dan Konseling, 2014)
Based on the phenomenon that researchers have found in the field obtained some information that the parental role is not going well. Thus, researchers from the incident raised concerns about the study: what is the role of parents in shaping the character of the child responsible. The purpose of the study to describe: 1) The role of parents in providing a wide range of homework assignments for children according to age. 2) The role of parents in providing role models responsible for the childs character. 3) The role of the parents to get children to participate security environment.This research is a descriptive qualitative research which seeks to describe the situation as it is. Informants of this research is all the parents and children of primary school age. Thus, the number of his informants are as many as 10 people consisting of 5 key informants that the parents and the child 5 additional informants. The instrument used in this study were interviews. The results of this study revealed that: 1) The role of parents in providing various kinds of homework assignments to the child in accordance with his age that the parental role is not perfect, 2) The role of parents in providing an example of exemplary character responsible for the child that the parents have not right thoroughly and give examples of exemplary character responsible for primary school aged children 3) the role of the parents to get children to participate security environment more stressed parents of children not to throw garbage everywhere, parents teach the child to engage in mutual assistance held in the neighborhood.